SCHOLARLY LEGAL DOCTRINES ON THE INVALIDITY OF TRANSACTIONS - Sattarov Omon Ilkhamovich (Ecominds Press, 2026)
This article analyzes the main scientific and legal doctrines related to the invalidity of transactions in civil law. In particular, the doctrines of absolute and relative invalidity, defects of transactions, convalidation, protection of legitimate expectations, partial invalidity, and the relativity of the consequences of invalidity are examined. The study also explores the development of these doctrines within foreign legal systems, especially within the framework of the German Pandect model. The author substantiates the importance of critically assessing and adapting these doctrines to the specific features of the national legal system in the process of improving the civil legislation of the Republic of Uzbekistan.
Keywords: Transaction, invalidity of transaction, civil law, legal doctrine, declaration of will, defective transaction, convalidation, protection of legitimate expectations, Pandect model.